(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: To determine the rate of anxiety and depression in gastrointestinal patients before and after surgery; to identify related factors; to propose intervention measures. Subject and method: A cross-sectional descriptive study on 218 surgical patients in the Gastrointestinal Surgery Department, Thong Nhat Hospital. The Beck scale was used to assess preoperative and postoperative psychological status. Results: Prior to surgery, 27-36% of patients had mild to moderate anxiety. After surgery, this rate decreased to 10-16%. Related factors included concerns about surgical outcomes, pain, complications. Conclusion: A proportion of patients still experienced anxiety and depression after surgery. Effective psychological support for patients is needed.